The Measurement of Land Conversion Rate and Household Food Security in Bakalan Village, Pasuruan Regency - Novianty, Puput Cindy; Soemarno, Soemarno; Efani, Anthon (Jurnal Pembangunan dan Alam Lestari, 2025)
This study investigates the land conversion rate and household food security in Bakalan Village, Pasuruan Regency. Data was collected through primary surveys, including detailed observations of land conversion and structured interviews with various residents, including ordinary households, farmer households, and farmer households with land conversion. The research employed quantitative methods to analyze the rate of land conversion and its implications on food security. Specifically, the study quantified the extent of land conversion and evaluated household food security using indicators such as food expenditure and energy consumption ratios. The findings revealed a substantial % land conversion rate of 50% between 2020 and 2021. This conversion was predominantly economically motivated, largely due to the influx of industrial development in the area. Significantly, converting land use from agriculture to industrial areas profoundly affected food security. The study found that overall food security in the village was compromised, with most households consuming less than the standard of 114.6 kg per person per year. This below-standard consumption was directly linked to energy deficiencies among the population. The results of this study underscore the urgent need for policy interventions that balance economic development with food security and sustainability. This research contributes to the broader discourse on land use planning and its critical implications for agricultural productivity and food security. These findings also provide valuable insights for policymakers, suggesting that development strategies should include provisions for safeguarding and enhancing food security in regions undergoing rapid industrialization. This study sets a foundation for future research in agricultural economics by illustrating the intricate connections between land use dynamics and food security outcomes. Keywords: agricultural economics, household food security, industrial development, land conversion rate